GENERAL METHOD OF STOCKS AUDIT - Galushchak , I.Ye. (The actual problems of regional economy development, 2017)
The article deals with the organization and methodology of accounting and auditing inventory enterprises. Suggestions for improvement of accounting permit to raise processing and presenting economic information to a higher level for making the economic and management decisions. Theory and practice problems of stocks audit were investigated. The basic directions of improvement of stock audit were defined. The auditor can form an opinion about the state of business transactions of accounting of goods, define shortcomings in its organization and possible directions of elimination of violations and abuses. Program of audit of operations accounting with stocks should include the investigation of the preservation of property, valuation and posting costs, correct evaluation of purchased tangible assets, using of stocks in production. It is worth to use techniques and methods of verification such as inventory, comparative control, comparison of documentary evidence, counter check, check arithmetic for audit of goods.